Time Constraints of Late Cenozoic Tectonic Deformation of the Atushi Anticline, Southwestern Tian Shan: Evidence From Cosmogenic Nuclide Burial Age - Chen, Qingyu; Fu, Bihong; Shi, Pilong; Kong, Ping (Frontiers in Earth Science, 2022)
With the latest uplift episode of Tian Shan occurring since early Miocene, a series of thrust–fold belts were formed in front of Tian Shan. The Kashi foreland thrust–fold belt (KFTB) provided a unique case to understand the ongoing intracontinental deformation within the Pamir–Tian Shan convergence zone (PTCZ). Previous cosmogenic nuclide chronological studies on growth folds suggested that the young thrust–fold belt in front of Pamir formed during 6–1.07 Ma. However, the age constraints of late Cenozoic deformation in front of southwestern Tian Shan are still debated. In this study, we attempt to constrain the initial deformation time of the NEE-striking Atushi anticline (ATA) in the KFTB through the cosmogenic nuclide burial dating data of growth strata near the boundary between Pliocene–Pleistocene Atushi Formation and Xiyu Formation (Xiyu Conglomerate), which are exposed in the southern limb of ATA. Moreover, detailed geological interpretations of multiple remote sensing images and field investigations are also carried out to document the late Cenozoic structural deformation and geomorphologic features of ATA. The 26Al/10Be burial dating data of four fine-grained samples reveal that the syntectonic deposit of ATA initiated at 1.79 ± 0.16 Ma, and the deposit of Xiyu Conglomerate started since 1.67 ± 0.18 Ma. Thus, we suggest that the thrust–folding of ATA began at ca.1.79 Ma and is currently still active.